The olivo-cerebellar system and its relationship to survival circuits - Watson, Thomas C.; Koutsikou, Stella; Cerminara, Nadia L.; Flavell, Charlotte R.; Crook, Jonathan; Lumb, Bridget M.; Apps, Richard (Frontiers in Neural Circuits, 2013)
How does the cerebellum, the brain’s largest sensorimotor structure, contribute to complex behaviors essential to survival? While we know much about the role of limbic and closely associated brainstem structures in relation to a variety of emotional, sensory, or motivational stimuli, we know very little about how these circuits interact with the cerebellum to generate appropriate patterns of behavioral response. Here we focus on evidence suggesting that the olivo-cerebellar system may link to survival networks via interactions with the midbrain periaqueductal gray, a structure with a well known role in expression of survival responses. As a result of this interaction we argue that, in addition to important roles in motor control, the inferior olive, and related olivo-cortico-nuclear circuits, should be considered part of a larger network of brain structures involved in coordinating survival behavior through the selective relaying of “teaching signals” arising from higher centers associated with emotional behaviors.